Higher education and employment related skills. The point of view of employers - Bartual Figueras, M. Teresa; Turmo Garuz, Joaquín (Revista Complutense de Educación, 2016)
The relevance of knowledge as an input in the productive process has increased the complexity of the process of hiring in the market of qualified work. As a consequence, a process of reflection on the adequacy of university accreditation to the needs of the labor market has generated. Academics, managers and experts in labor market of highly skilled workers have taken part in this reflection for a long time. This paper aims to identify the most relevant professional competencies in the employability of graduates in Economics and Business. The analysis is based on a qualitative research which adopts the opinions of employers as its source of information. This information has been obtained through thorough interviews and a discussion group. Entrepreneurs, managers of student practices of the University of Barcelona, labor market, experts, representatives of business organizations, and academics, have participated in the process. Attention is focused on the perception of the interviewees regarding the required knowledge, skills and attitudes, the extent to which developed those abilities and the changes that would be needed to achieve a better match between the acquired competencies and those required by the labor market. Taking into account the classification of skills carried out in this study (Tuning Project), we conclude that employers particularly value generic skills. However, there are evaluative differences depending on the type of companies. In addition, deficiencies are also evidenced in relevant aspects, such as practical training and in initiative, analytical or organization skills. Lastly, opinions of respondents also suggest that it would be convenient to bring closer the Universities and enterprises, at least in the economic and business fields.
Keywords: higher education; professional skills; employment; business administration graduates